The Effect Of Income Tax Rate, Bonus Mechanism, And Tunneling Incentives On Transfer Pricing (Empirical Study Of Multinational Manufacturing Companies Listed On The Indonesia Stock Exchange 2018 - 2022) - Mega Utami; Harti Budi Yanti (UNIVED Press, 2025)
This study explores the influence of income tax rates, bonus mechanisms, and tunneling incentives on transfer pricing decisions within multinational manufacturing companies from 2018 to 2022. In an era of globalization, companies operating across multiple countries face varied tax regulations, making transfer pricing a crucial aspect of financial strategy and compliance. A total of 66 samples were selected using purposive sampling based on specific characteristics, utilizing secondary data obtained from annual reports on www.idx.co.id. The research employs logistic regression analysis, with hypothesis testing conducted using the t-test at a 5% significance level (α = 0.05), and SPSS 27 software as the statistical tool. The results indicate that income tax rates (sig. 0.153 > 0.05) and bonus mechanisms (sig. 0.449 > 0.05) do not significantly affect transfer pricing decisions. However, tunneling incentives exhibit a significant negative effect (sig. 0.010 < 0.05), suggesting that companies with higher tunneling incentives are less likely to engage in transfer pricing practices. The Adjusted R Square value of 49.7% suggests that nearly half of the variation in transfer pricing is explained by the model, while 50.3% is due to other unobserved variables. The findings offer valuable insights for financial managers and policymakers to strengthen transfer pricing regulations and improve tax compliance.